Pelatihan Bahasa Arab: Mufrodat Al-‘Adad 1-10 dengan Metode Pembelajaran Interaktif pada Anak-Anak di Majelis Darul Anwar Kampung Sukajaga Cihanjawar Purwakarta - Limah Nurlatipah; Rohendi Rohendi; Taufik Luthfi; Riyan Haqi Khoerul Anwar (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2025)
The The Arabic language training on mufrodat al-‘adad (numbers 1-10) at Majelis Darul Anwar, Kampung Sukajaga, Cihanjawar utilized an interactive learning method, including singing and educational games, to enhance children's understanding. Using the Participatory Action Research (PAR) method, the training followed stages of observation, licensing, socialization, implementation, and evaluation. The results indicate that this approach effectively helps children recognize numbers 1-10 in Arabic more easily and enjoyably. The main challenge was the differences in children's educational backgrounds, requiring varied learning media and continuous training. It is recommended to expand the material scope and establish collaboration with local educational institutions to support program sustainability.